Pauli–Villars regularization elucidated in Bopp–Podolsky’s generalized electrodynamics - Chueng-Ryong Ji; Alfredo Takashi Suzuki; Jorge Henrique Sales; Ronaldo Thibes (European Physical Journal C: Particles and Fields, 2019)
Abstract We discuss an inherent Pauli–Villars regularization in Bopp–Podolsky’s generalized electrodynamics. Introducing gauge-fixing terms for Bopp–Podolsky’s generalized electrodynamic action, we realize a unique feature for the corresponding photon propagator with a built-in Pauli–Villars regularization independent of the gauge choice made in Maxwell’s usual electromagnetism. According to our realization, the length dimensional parameter a associated with Bopp–Podolsky’s higher order derivatives corresponds to the inverse of the Pauli–Villars regularization mass scale $$\Lambda $$ Λ , i.e. $$a = 1/\Lambda $$ a=1/Λ . Solving explicitly the classical static Bopp–Podolsky’s equations of motion for a specific charge distribution, we explore the physical meaning of the parameter a in terms of the size of the charge distribution. As an offspring of the generalized photon propagator analysis, we also discuss our findings regarding on the issue of the two-term vs. three-term photon propagator in light-front dynamics.